Involvement of ADGRV1 Gene in Familial Forms of Genetic Generalized Epilepsy - Dahawi, Maha; Elmagzoub, Mohamed S.; A. Ahmed, Elhami; Baldassari, Sara; Achaz, Guillaume; Elmugadam, Fatima A.; Abdelgadir, Wasma A.; Baulac, Stéphanie; Buratti, Julien; Abdalla, Omer; Gamil, Sahar; Alzubeir, Maha; et al. (Frontiers in Neurology, 2021)
Background: Genetic generalized epilepsies (GGE) including childhood absence epilepsy (CAE), juvenile absence epilepsy (JAE), juvenile myoclonic epilepsy (JME), and GGE with tonic-clonic seizures alone (GGE-TCS), are common types of epilepsy mostly determined by a polygenic mode of inheritance. Recent studies showed that susceptibility genes for GGE are numerous and their variants rare, challenging their identification. In this study, we aimed to assess GGE genetic etiology in a Sudanese population. Methods: We performed whole-exome sequencing (WES) in 40 patients'DNA from 20 Sudanese families with GGE searching for candidate susceptibility variants, which were prioritized by CADD software and functional features of the corresponding gene. We assessed their segregation in 138 individuals and performed genotype-phenotype correlations. Results: In a family including 3 sibs with GGE-TCS, we identified a rare missense variant in ADGRV1 encoding an adhesion G protein-coupled receptor V1, which was already involved in the autosomal recessive Usher type C syndrome. In addition, 5 other ADGRV1 rare missense variants were identified in four additional families and absent from 119 Sudanese controls. In one of these families, an ADGRV1 variant was found at a homozygous state in a female more severely affected than her heterozygous brother, suggesting a gene dosage effect. In the 5 families, GGE phenotype was statistically associated with ADGRV1 variants (0R=0.9 103). Conclusion: This study highly supports for the first time that ADGRV1 missense variants are involved in familial GGE and that ADGRV1 is a susceptibility gene for CAE/JAE and GGE-TCS phenotypes.